A Bird's-Eye View of Cell Sources for Cell-Based Therapies in Blood Cancers - Motais, Benjamin; Charvátová, Sandra; Hrdinka, Matouš; Šimíček, Michal; Jelínek, Tomáš; Ševčíková, Tereza; Kořístek, Zdeněk; Hájek, Roman; Bagó, Juli R (Cancers, 2020)
: Hematological malignancies comprise over a hundred different types of cancers and account for around 6.5% of all cancers. Despite the significant improvements in diagnosis and treatment, many of those cancers remain incurable. In recent years, cancer cell-based therapy has become a promising approach to treat those incurable hematological malignancies with striking results in different clinical trials. The most investigated, and the one that has advanced the most, is the cell-based therapy with T lymphocytes modified with chimeric antigen receptors. Those promising initial results prepared the ground to explore other cell-based therapies to treat patients with blood cancer. In this review, we want to provide an overview of the different types of cell-based therapies in blood cancer, describing them according to the cell source.
Keywords: CAR-T cells; dendritic cells; iPSC; NK cells; platelets; macrophages; blood cancer; stem cells; cell-based therapy